P-79 Lessons for comprehensive, person-centred carer assessment and support from the CSNAT intervention. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Ewing, Gail; Grande, Gunn; Diffin, Janet; Austin, Lynn
Abstract : Background: The Carer Support Needs Assessment Tool (CSNAT) intervention comprises an evidence-based comprehensive tool incorporated into a person-centred process of assessment and support for carers of people with life-limiting conditions. It was developed from a programme of research, subsequently implemented across practice settings (community, hospital, hospice). The CSNAT's impact nationally and internationally is substantial: 87 UK services are licensed to use the intervention, the tool has been translated into 13 languages, and is used in 27 countries. Aim: To draw on the CSNAT intervention programme of research to illustrate why carer assessment needs to be comprehensive and person-centred, how this represents a change in practice, what difference it makes, and how this change in practice can be implemented. Methods/results: We will draw on three aspects of the research programme: An overview of development, validation and initial implementation of the CSNAT: a qualitative study with 75 bereaved carers (01/2008–12/2008) identified the 14 support need domains that constitute the CSNAT; a survey of 225 current carers (04/2009–06/2010) established CSNAT's content and criterion validity; implementation studies with 29 practitioners in two hospices (08/2010–12/2010; 01/2011–04/2012) identified use of the CSNAT as a significant change in practice and the importance of adopting a person–centred approach. Two cluster randomised control trials of the CSNAT intervention (UK: n=681 carers; 05/2012–11/2014); (Australia: n=322 carers; 03/2012–02/2014) showed a reduction in caregiver strain in current carers, and lower early grief and better physical/mental health in bereavement. A national implementation study in 36 organisations (11/2013–09/2014) and a hospice case study (11/2015–12/2016) provided key insights into practitioners' training needs and vital organisational structures/processes needed to embed the intervention in practice, to underpin a CSNAT intervention Training and Implementation Toolkit. Conclusion: This paper identifies the evidence base for the CSNAT intervention and lessons learnt about delivery of comprehensive, person-centred carer assessment and support for family carers.